Development of a Discovery Learning-Based E-Book of English Learning Activities to Enhance Junior High School Students’ Learning Engagement - Ariani, Vika; Era Adnyayanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop an e-book containing a guide to English learning activities based on the Discovery Learning approach, designed to enhance the learning engagement of eighth-grade junior high school students. The background of this development stems from initial findings indicating low levels of student engagement in learning, both cognitively, emotionally, and behaviorally. The study employs the ADDE development model (Analysis, Design, Development, Evaluation), which consists of four main stages. Initial data were collected through classroom observations, teacher interviews, and document analysis to understand the current learning conditions and the needs of teachers. The resulting product is an e-book that includes learning activities along with teacher instructions, student activities, engagement focus, assessment, and teacher reflection. Expert validation results indicate that the e-book is feasible to use in terms of content, design, and alignment with the principles of Discovery Learning. These findings suggest that the e-book has the potential to serve as an effective learning medium that actively promotes student engagement. Keywords: Discovery Learning, E-book, English Language Learning, Learning Engagement